An autopsy case of a centenarian with the pathology of senile dementia of the neurofibrillary tangle type. Issue 2 (13th July 2016) - Iwasaki, Yasushi; Deguchi, Akira; Mori, Keiko; Ito, Masumi; Mimuro, Maya; Yoshida, Mari
Abstract : A Japanese woman showed slowly progressive memory disturbance since the age of 85 years. Later, disorientation gradually appeared. Head computed tomography revealed severe hippocampal atrophy, particularly in the posterior portion, and lateral ventricular dilatation, particularly in the inferior horn at the age of 99 years. The amygdala was relatively preserved from atrophy, and atrophy of the frontal lobe was relatively mild for her age. Apolipoprotein E gene analysis showed the ε3 homozygous phenotype. The woman died at the age of 101 years, and her clinical diagnosis was mild Alzheimer's disease. No apparent behavioural and psychological symptoms of dementia were observed during the disease course. Autopsy revealed severe hippocampal atrophy with numerous neurofibrillary tangles and ghost tangles, particularly in the hippocampal region, but senile plaques were rarely observed in the brain. The pathological findings were compatible with senile dementia of the neurofibrillary tangle type, whereas other neurodegenerative disorders were not recognized. The clinicopathologic findings of the present case are considered significant for the clinical diagnosis and pathogenesis of senile dementia of the neurofibrillary tangle type.